Esamojo laiko formantas -st- išvestiniuose lietuvių kalbos veiksmažodžiuose - Pakerys, Jurgis (Baltistica, 2007)
Lithuanian secondary verbs based on present stems in ‑staLithuanian has a number of deverbative formations which are clearly based on present stems, cf.: ded‑ẽklė ‘good layer (about hens)’ : dẽd‑a ‘lays’, dúod‑ingas ‘open‑handed, generous’, duod‑imas ‘giving’ : dúod‑a ‘gives’, verd‑ẽnė ‘spring’ : vérd‑a ‘boils’, es‑ìmas ‘being’ : es‑ù ‘I am’, ẽs‑ti ‘it is’, tek‑ìmas ‘rising (of the sun)’ : tẽk‑a ‘flows, runs; rises (the sun)’ (beside tekė́ti, ‑ė́jo and tekė́jimas), lim̃p‑alas ‘sticky material’ : li‑m̃‑p‑a ‘sticks’, skrand‑nùs ‘good flyer’ : skre‑ñ‑d‑a ‘flies’, kánk‑inti(s) ‘to give enough, to satisfy’ : (pa)ka‑ñ‑k‑a ‘suffices’, té‑n‑k‑inti ‘to satisfy’ : (už)te‑ñ‑k‑a ‘suffices’, trunk‑imas ‘delaying’ : tru‑ñ‑k‑a ‘lasts, delays’, etc. (Būga 1959, 446; Urbutis 1978, 191, 197; Ambrazas 1993, 21‑25).This paper presents examples of Lithuanian secondary verbs based on present stems in ‑sta, cf. pýkst‑auti ‘to be angry’ : pỹkst‑a ‘is angry’. These formations represent a rare (archaic?) derivational process and they can be used to support the hypothesis of the deverbative origin of suffix ‑styti (Latvian ‑stīt). The proponents of this hypothesis believe that present stems in ‑sta provided bases for some formations in ‑yti (‑o, ‑ė) which were later resegmented and gave rise to new suffix ‑styti (‑sto, ‑stė), cf.: lankst‑ýti : liñkst‑a → lank‑stýti : leñk‑ti (Ul’janov 1888, 210; Leumann 1942, 125; Vaillant 1966, 364; Smoczyński 1987, 203). On the other hand, the data presented in this paper still do not exclude the possibility of denominal origin of ‑styti (Leskien 1884, 443; Johanson 1893, 502; Endzelin 1922, 641; Skardžius 1943, 538; Stang 1942, 149; cf. Jasanoff 2003, 141).All material was excerpted from the electronic edition of “Lietuvių kalbos žodynas” (http://www.lkz.lt) and arranged according to suffixes.The class of verbs in ‑auti has 8 formations which are based on the stems in ‑sta: blė́stauti ‘to burn lightly, to be burning down’ : blė́sta ‘burns down’, nubostauti ‘to ask for something in a bothersome way’ : nubósta ‘gets bored, becomes boring’, nerimstauti ‘to be bored, to wander’ : nerìmsta ‘is not calm’, nirštauti ‘to be (slightly) angry’ : nir̃šta ‘is angry, rages’, pýkstauti ‘to be angry’ : pỹksta ‘is angry’, širstauti ‘to rage’ : šir̃sta ‘rages’, trókštauti ‘to desire’ : trókšta ‘desires’, vargstáuti ‘to live in trouble, to have difficulties’ : var̃gsta ‘lives in poverty, takes trouble’.The class in ‑enti provides 3 examples: birsténti ‘to scatter, to strew (slightly)’ : (dialectal) bìrsta ‘pours out (intr.)’ (therefore, the formation is causative), blėsténti ‘to burn slightly, to go out’ : blė́sta ‘burns down’, rūksténti ‘to emit smoke little by little’ : rū̃ksta ‘emits smoke’.The formations in ‑ėti based on the stems in ‑sta are the following: drįstė́ti, ‑ė́ja ‘to dare’ : drį̃sta ‘dares’, numirštė́ti, ‑ė́ja ‘to die (about animals)’ : numìršta ‘dies’, plū́stėti, plū́sta ‘to talk nonsense’ : plū́sta ‘talks nonsense’, rūkstė́ti, ‑ė́ja ‘to emit smoke’ : rū̃ksta ‘emits smoke’, smilkstė́ti, smil̃ksta ‘to burn without fire, to smoulder’ : smil̃ksta ‘smoulders’, spurstė́ti, spùrsta ‘to flounder’ : spùrsta ‘flounders’, várgstėti, ‑ėja ‘to live in trouble, to have difficulties’ : var̃gst‑a ‘lives in poverty, takes trouble’. It is possible that in some cases the verbs were not really derived, but rather reshaped according to the model of tekė́ti, tẽka (the inflectional stems in ‑st‑(a) became lexical), e. g. tẽk‑a : smil̃kst‑a, tek‑ė́‑ti, ‑ė́jo : x, x = smilkst‑ė́‑ti, ‑ė́‑jo. A number of similar remodelings or derivations are also based on 3 person athematic forms reinterpreted as the members of i stem paradigms, cf.: susičiáustėti, ‑i ‘to cough’ : susičiáust‑i ‘coughs’, ráustėti, ‑ėja ‘to weep’ : ráust‑i ‘weeps’, prisérgstėti, ‑ėja ‘to watch over, to guard’ : prisérgst‑i ‘watches over, guards’.The class in ‑inėti provides 6 formations directly derived from the stems in ‑sta: dilbstinė́ti ‘to loiter, to hang around’ : dil̃bsta ‘loiters’, dygstinė́ti ‘to shoot, to start to grow little by little’ : dýgsta ‘starts to grow’, mirštinė́ti ‘to die constantly (about a moderate number of deaths occurring during a certain period of time)’ : mìršta ‘dies’, plūstinė́ti ‘to wander’ : plū́sta ‘wanders’, snūstinė́ti ‘to walk sleepy’ : snū́sta ‘snoozes’, virstinė́ti ‘to fall down repeatedly, to sway’ : vir̃sta ‘falls down’.The class in -inti has 4 verbs based on the stems in -sta: bìrstinti ‘to scatter, to strew (slightly)’ : (dialectal) bìrsta ‘pours out (intr.)’, ìlgstinti ‘to linger, to delay’ : ìlgsta ‘becomes long’, pùrstintis ‘to put on airs’ : pur̃sta ‘swells’, virstinti ‘to come swaying’ : vir̃sta ‘falls down’. One should note that at least two formations are causative (bìrstinti and pùrstinti).The formations in ‑yti possibly based on the stems in ‑sta are the following: džiáustyti ‘to dry (trans.)’ : džiū́sta ‘dries (intr.)’ (cf. iterative džiáustyti ‘to hang out to dry’ : džiáuti ‘idem’), gąstýtis ‘to be afraid’ : gą̃sta ‘becomes frightened’, gramstýti ‘to plunge (repeatedly)’ : grim̃zta ‘sinks, plunges’, ilgstytis ‘to become long’ : ìlgsta ‘becomes long’, raibstytis ‘to be dazzled’ : raĩbsta ‘is dazzled’, (ne)įrìmstyti (‑ija) ‘(not) to calm down (intr.)’ : nerìmsta ‘is not calm’, nurìmstyti ‘to calm down (trans.)’ : nurìmsta ‘calms down’, slū́gstyti ‘to make (swelling) go down’ : slū́gsta ‘(swelling) goes down’, svaigstytis ‘to wander’ : svaĩgsta ‘to start feeling dizzy, to become delirious’. A number of these verbs can also be simple derivations in ‑styti, but at least causative cases (džiáustyti, nurìmstyti, slū́gstyti) are more reliable examples as this meaning is not typical for the formations in ‑styti.There are no good examples of verbs in ‑oti which could be based on the present stems in ‑sta. However, one should note that there is a small group of verbs which seem to have an independent suffix ‑stoti, ‑stoja, cf. išėstóti (the present stem is not attested) ‘to wipe out’ : (iš)ė́sti, ė́da, ė́dė ‘to eat away’; laipstoti, ‑oja ‘to climb, to fly (repeatedly)’ : lìpti, lìpa, lìpo ‘to climb’, lakstóti, ‑ója ‘to fly about’ : lė̃kti, lẽkia, lė̃kė ‘to fly’, užžirstóti (the present stem is not attested) ‘to become covered by falling particles’ : (už)žìrti (žir̃ti), žỹra (also žìrsta), žìro ‘to fall, to scatter’. These examples could reflect a well known variation of present (factitive and iterative) stems in *‑ā and *‑āja (cf. Lith. mė́tyti, mė́to beside mė́toti, mė́toja (rare), Latv. mę̃tât, mę̃tãju, OCS mětati, mětajǫ, Lith. statýti, stãto : statùs (stãtas) beside bjaurója : bjaurùs (bjaũras)).There are 2 formations in ‑uoti which can be directly related to the base stems in ‑sta: ilgstuoti ‘to linger, to delay’ : ìlgsta ‘becomes long’, linkstúoti ‘to bend (intr.)’ : liñksta ‘bends’.
Keywords: veiksmažodis; esamasis laikas